2017
DOI: 10.3389/fnana.2017.00085
|View full text |Cite
|
Sign up to set email alerts
|

A Connectomic Analysis of the Human Basal Ganglia Network

Abstract: The current model of basal ganglia circuits has been introduced almost two decades ago and has settled the basis for our understanding of basal ganglia physiology and movement disorders. Although many questions are yet to be answered, several efforts have been recently made to shed new light on basal ganglia function. The traditional concept of “direct” and “indirect” pathways, obtained from axonal tracing studies in non-human primates and post-mortem fiber dissection in the human brain, still retains a remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 71 publications
7
55
1
Order By: Relevance
“…The corticostriatal connectivity has been generally considered a rich set of pathways between the putamen and the caudate with frontal and parietal regions. Previous findings have shown that caudate is principally connected with the frontal cortex, such as the ventral PFC, superior frontal gyrus, rostral middle frontal gyrus, and orbitofrontal gyrus (Cacciola et al, 2017). In contrast to the latter study, the data presented in the current report revealed decreased intra-basal-ganglia-connection and absence of suprathreshold connections in the frontal or parietal area with caudate.…”
Section: Discussioncontrasting
confidence: 99%
“…The corticostriatal connectivity has been generally considered a rich set of pathways between the putamen and the caudate with frontal and parietal regions. Previous findings have shown that caudate is principally connected with the frontal cortex, such as the ventral PFC, superior frontal gyrus, rostral middle frontal gyrus, and orbitofrontal gyrus (Cacciola et al, 2017). In contrast to the latter study, the data presented in the current report revealed decreased intra-basal-ganglia-connection and absence of suprathreshold connections in the frontal or parietal area with caudate.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, our results, in line with previous investigations, 23,25,70 may suggest the possible existence of a direct dento-pallidal connection in the human brain. Although highly speculative, it can be hypothesized that a direct dento-pallidal route may represent a fast conducting system that appeared phylogenetically later, in humans, triggered by the emergent importance of manual dexterity.…”
Section: Discussionsupporting
confidence: 93%
“…15,16 More recently, we used constrained spherical deconvolution (CSD)-based tractography, a diffusion MRI-based technique allowing in vivo reconstruction of connectivity patterns between nervous structures, [17][18][19][20][21] to study the human analogues of the above-mentioned direct cortico- 22 and dento-pallidal projections. 23 These connections, likely paralleled by analogue cortico- 24 and dento-nigral 23,25 pathways, may exert a converging influence of cerebral and neocerebellar cortex on the basal ganglia output nuclei.…”
mentioning
confidence: 99%
“…The findings of Ni and associates are also in line with recent human structural connectomics data showing that precentral and postcentral gyri, the paracentral and superior parietal lobules, are connected with GP paralleling the direct, indirect, and hyperdirect pathway . The existence of a direct cortico‐pallidal connection is also corroborated by the presence of a robust band of beta coherence between the sensorimotor areas and GPi in dystonic patients with GPi‐DBS .…”
supporting
confidence: 83%